The role of learning in improving functional writing in stroke aphasia. Issue 21 (8th October 2016) - Thiel, Lindsey; Sage, Karen; Conroy, Paul
Abstract: Purpose: Improving writing in people with aphasia could improve ability to communicate, reduce isolation and increase access to information. One area that has not been sufficiently explored is the effect of impairment based spelling therapies on functional writing. A multiple case study was conducted with eight participants with aphasia subsequent to stroke. This aimed to measure the effects of spelling therapy on functional writing and perception of disability. Method: Participants engaged in 10 sessions of copy and recall spelling therapy. Outcome measures included spelling to dictation of trained and untrained words, written picture description, spelling accuracy within emails, a disability questionnaire and a writing frequency diary. Results: All participants made significant gains on treated words and six demonstrated improvements to untreated words. Group analyses showed significant improvements to written picture description, but not email writing, writing frequency or perceptions of disability. Conclusions: These results show that small doses of writing therapy can lead to large gains in specific types of writing. These gains did not extend to improvements in frequency of writing in daily living, nor ecological measures of email writing. There is a need to develop bridging interventions between experimental tasks towards more multi-faceted and ecological everyday writing tasks. Implications for Rehabilitation: Acquired dysgraphia can restrict people from participating in social, educational and professional life. This study has shown that copy and recall spelling therapies can improve the spelling of treated words, untreated words and written picture description in people with a range of types and severities of dysgraphia following stroke. The results of this study suggest that more specific additional training is required for other writing activities such as email writing.